Activities, games, and lessons for social learning : a practical guide - Erdelyi, Julie; Buron, Kari Dunn (Thousand Oaks : CORWIN, 2020)
In these games, the prize is success in school-and life. Having good social skills doesn't just affect classroom behavior-it's the key to making learning stick. When students improve their self-regulation, social communication, and perspective-taking competencies, they are better prepared to challenge themselves academically, take on tough tasks, and collaborate with teachers and classmates to achieve real, lasting school success. And since these skills also improve life outside school, the benefits come full circle. Designed for both explicit instruction and'learning by doing,' this practical guide provides hands-on activities that are easily adapted into any curriculum and can be used in general education, special education, after-school settings, and in the home. The design of each game keeps kids engaged and motivated, while educators benefit from clear, thorough explanations that unpack the complexities of social learning. Other behind-the-scenes features include: Evidence-based, teacher-tested lessons Anecdotes and real-world examples Links to relevant research Expansion ideas for applying learned skills to broader situations Templates and reproducibles for easy implementation This curated collection of activities puts social-learning theory into practice, helping even the most challenging children develop the social skills necessary for real success in school-and beyond.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Social learning -- Study and teaching